Improved Antihyaluronidase Test Applicable to the Microtitration Technique - Murphy, Richard A. (1972)
The incorporation of India ink into the substrate solution in a standard antihyaluronidase test has facilitated the reading of end points in the standard tube dilution test and has made possible an antihyaluronidase microtiter test.